From Pressure to Water Consumption: Exploiting High-Resolution Pressure Data to Investigate the End Uses of Water - Marsili, Valentina; Mazzoni, Filippo; Alvisi, Stefano; Franchini, Marco (Water resources management, 2024)
Highlights A method to investigate water consumption based on pressure data is developed. The method exploits the headloss-flowrate equation to obtain water-consumption data. The method is validated on a real case study, resulting in an average error of 2.3%. Limitations affecting the installation of domestic flow meters are overcome. Insights into the features of individual water-consumption events are provided. In the era of digital transformation of water distribution networks, an increasingly important role is played by smart metering technologies, which allow detailed characterization of water consumption up to the end-use (i.e., domestic-fixture) level. To this end, smart flow meters make the collection of water-consumption data at high temporal resolution possible, but their installation can be unfeasible due to technical and economic limitations. As an alternative to the traditional flow-measurement-based methods for end-use characterization, a pragmatic method to obtain information about end-use water consumption exclusively based on pressure data is proposed in this study. In particular, a dual-phase methodology is developed, exploiting (i) pressure data collected at two sections of the user’s inlet pipeline and (ii) the pressure-flowrate relationship to discriminate between internal and external water-use events and estimate the household water-consumption time series, which is then subjected to individual-event analysis. The results obtained on a real case study undergone to 1-s resolution pressure monitoring over about one month and a half confirm the method’s effectiveness in obtaining the flowrate time series with an average error of about 2.3% and successfully identifying water-consumption events along with their features. Graphical Abstract